KCPR Public Affairs Broadcast: Special Program on Non-Retention of Instructors - KCPR::::::::: (1971)
[00:00:02] the following is a special program dealing with the issue of non-retained professors at Cal Poly; the program is back and forth audio clips from various professors and faculty giving their reasoning on the issue [00:00:09] program theme song [00:00:15] Dr. Rizzo reads a quote about his actions being incompatible with his college responsibilities [00:00:35] Dr. Ralph Vrana of the physics department states the dean did not approve his recommendation for tenure [00:01:02] President Kennedy says it is not true that these professors are not being retained [00:01:17] Dr. Vrana explains why he does not think his lack of a doctorate is why he is not being rehired [00:02:14] Dr. Rizzo reads a memo between Robert E. Kennedy and James Landreth [00:02:53] Raymond DeGrudio from SNAP says the American Legion newsletter is a relevant form of criticism in the evaluation of instructors [00:03:05] Dr. Robert Kennedy comments on treating the memo he received the same as all other mail [00:04:20] Dr. Rizzo comments on Kennedy is not fit for the university presidency for allowing the American Legion to criticize his anti war attitude [00:04:46] radio host asks where this discussion is leading the university [00:05:02] Dr. Rizzo says the formal reason for not receiving tenure is "subordination" for refusing to instruct a freshman class [00:05:36] Dr. John Ericson says he will always put political things in people's files [00:06:29] Dr. Kennedy points to the grievance system for addressing these problems [00:07:02] Dr. Rizzo explains the issue of which classes he was supposed to instruct [00:08:05] states that the chairman assigned him the task of circulating a petition towards the North Vietnamese about POW treatment [00:08:52] Rizzo calls the petition hypocritical in the Mustang Daily but circulated it anyway [00:09:34] Rizzo discusses the personal antagonism between him and his chairman [00:10:47] Rizzo talks about the political considerations in his case because of the American Legion newsletter in his file and his opinions on the Vietnam War and its military draft [00:13:10] Dr. Kennedy calls this an "after-the-fact" situation as his interpretation of Rizzo's cooperation [00:13:30] host summarizes the information from the various audio quotes [00:14:05] host says the problem is not why Rizzo is not retained, but what is being done about it [00:14:10] Rizzo highlights the built in defense against dissidence at Cal Poly, and that only students can take the power back [00:14:45] Rizzo reads a quote from his chairman of the evaluation committee, who says Rizzo's status as a controversial figure on campus could be useful if kept in line [00:15:32] Says it is wrong for the school to go against the original contract which did not require Ph.D to work [00:16:02] Dr. Vrana say students are interested in this issue because they are concerned in subject matter and the non-retained instructors have much to offer in that field and that politics have played too large of a part in these decisions [00:16:30] radio hosts states Vrana has been offered tenure if he works toward a doctorate and that Rizzo will not be retained [00:16:41] host closes program